2019
DOI: 10.1177/0021998319877221
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption capacity of composite thin-wall circular tubes under axial crushing with different trigger initiations

Abstract: The purpose of this study is to evaluate and compare the ability of various composite structures to dissipate the energy generated during a crash. To this end, circular composite tubes were tested in compression in order to identify their behavior and determine their absorbing capabilities using the specific energy absorption (energy absorbed per unit weight). Several composite tubular structures with different materials and architectures were tested, including hybrid composition of carbon–aramid and hybrid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…sequence [49] (Fig. 18) and can reach 227 J/g in presence of PEEK resin with a tube 55 mm in diameter and 2.66 mm thick [50].…”
Section: Discussionmentioning
confidence: 99%
“…sequence [49] (Fig. 18) and can reach 227 J/g in presence of PEEK resin with a tube 55 mm in diameter and 2.66 mm thick [50].…”
Section: Discussionmentioning
confidence: 99%
“…Chambe et al [23] showed that for tubular CFRP coupons, outward splaying of the entire laminate results in a decrease in crush efficiency (up to 20% when compared to symmetric splaying), since inward splaying plies would offer more energy absorption due to the friction between the fronds that form. The crushing load responses of the three tested SISs are presented in Figure 20b.…”
Section: Side Impact Structuresmentioning
confidence: 99%
“…round tube [13][14][15][16], square tube [11,17,18], double hat [19]) geometries, for a variety of unidirectional (UD), 2D, and 3D woven and braided architectures. The effects of different triggers [5,7,20,21] and plug initiators [22,23] on the development of different failure mechanisms have also been extensively investigated. Conflicting results have been reported on the effects of dynamic crushing on the Specific Energy Absorption (SEA) of materials.…”
Section: Introductionmentioning
confidence: 99%
“…To account for repeatability, tube specimens were tested at least 3 to 5 times on average for each sample and each configuration. More details on experimental testing conditions and results can be found in a companion paper (see [50]).…”
Section: Test Set-up and Configurationsmentioning
confidence: 99%